A Case of Meningomyelocele in a Kindred with Multiple Cases of Spondylolisthesis and Spina Bifida Occulta. Issue 1 (March 1974) - Sever, Lowell E.
Abstract : A child with meningomyelocele, and other spinal anomalies, was born to a woman with three sibs who had spondylolisthesis and whose father and two of his sibs had a history of back problems. The suggestion is made that these anomalies represent a pattern of autosomal dominant inheritance with variable expressivity.